International Paediatric Mitochondrial Disease Scale. Issue 5 (9th June 2016) - Koene, Saskia; Hendriks, Jan C. M.; Dirks, Ilse; de Boer, Lonneke; de Vries, Maaike C.; Janssen, Mirian C. H.; Smuts, Izelle; Fung, Cheuk‐Wing; Wong, Virginia C. N.; de Coo, I. René F. M.; Vill, Katharina; Stendel, Claudia; et al.
Abstract: Objective: There is an urgent need for reliable and universally applicable outcome measures for children with mitochondrial diseases. In this study, we aimed to adapt the currently available Newcastle Paediatric Mitochondrial Disease Scale (NPMDS) to the International Paediatric Mitochondrial Disease Scale (IPMDS) during a Delphi‐based process with input from international collaborators, patients and caretakers, as well as a pilot reliability study in eight patients. Subsequently, we aimed to test the feasibility, construct validity and reliability of the IPMDS in a multicentre study. Methods: A clinically, biochemically and genetically heterogeneous group of 17 patients (age 1.6–16 years) from five different expert centres from four different continents were evaluated in this study. Results: The feasibility of the IPMDS was good, as indicated by a low number of missing items (4 %) and the positive evaluation of patients, parents and users. Principal component analysis of our small sample identified three factors, which explained 57.9 % of the variance. Good construct validity was found using hypothesis testing. The overall interrater reliability was good [median intraclass correlation coefficient for agreement between raters (ICCagreement ) 0.85; range 0.23–0.99). Conclusion: In conclusion, we suggest using the IPMDS for assessing natural history in children with mitochondrial diseases. These data should be used to further explore construct validity of the IPMDS and to set age limits. In parallel, responsiveness and the minimal clinically important difference should be studied to facilitate sample size calculations in future clinical trials.